Are the Malays really friendly? Contesting Norton's construct of a friendly communicator. - Ibrahim, Faisal; Ahmad, Abd Mua'ti @ Zamri; Tamam, Ezhar; Bolong, Jusang (SEGi University College, 2011)
This paper discusses the prevalence of the friendly -Malay notion that is based on Norton’s communicator style measurement (CSM) and seeks to contest the constructs used to measure friendly style from the Malay cultural perspectives. The data were collected in a field experiment where 21 pairs of the Malay-Chinese participants were individually asked to fill out a set of five 40-item questionnaire. The descriptive statistics and Pears on-Moment correlation test were used and the bases for contesting Norton’s construct of a friendly style are discussed.